Building local partnership through community parks in Central Tokyo: perspectives from different participants - Zong, Min; Xu, Guolin; Yanai, Shigeto (Frontiers in Sustainable Cities, 2024)
Globally, an increasing number of small urban green spaces are characterized by aging facilities and annual increases in maintenance and management costs. This is especially true when the available land area in city centers is limited and municipalities can only consider creating small urban green spaces. To revitalize and manage community parks more flexibly and ensure that green spaces benefit local communities, we selected three community parks in Toshima Ward, Tokyo, where multiple partners are involved in the revitalization of the parks, and conducted interviews with seven stakeholders and a questionnaire survey with 176 residents. The results of this study found that the priority circumstances for community participation in the revitalization of community parks included public buildings inside and outside the parks, sufficient green ery and open spaces, and local responsible persons; the low willingness of residents to participate posed a challenge to the revitalization of the multi-partner participation. In addition, experiencing different from usual, increasing the use of parents and children, motivating to go to the park, and increasing interaction opportunities are regarded by residents as the main impact brought by the engagement activities; markets, parent-child activities, and nature activities are suitable to be engagement activities at the community level. Finally, strategies to promote the participation of activities in community parks and increase the number of operating partners are proposed in light of the needs of different groups of people. This study proposes specific implementation strategies for the participation of multiple partners in the revitalization of community parks, which may serve as a reference for more cities around the world in promoting broader participation and collaborative practices in community green spaces.